Greenland – from Autonomy to (In)Dependence - BRAŃKA, Tomasz (Przegląd Strategiczny, 2018)
The purpose of this paper is to analyze the process of development of Greenland’s autonomy, especially vis-à-vis the Act on Greenland Self-Government of 2009, which ensures that decisions on the future status of the island will be made by the people of Greenland. Compared to other entities, Greenland is the only Arctic territory which can feasibly gain independence. This study also discusses the relations between Denmark and Greenland in terms of post-colonial relations between the former metropolis/colonizer and the island, outlining also the discourse on independence in Greenland. The hypothesis posed in the paper is that the proceeds from mineral extraction will not enable Greenland to become economically independent and abandon Danish subsidies, and that the process of gaining sovereignty might result in Greenland becoming dependent on external powers which will have a considerable impact on social relations on the island. This means that the matter under negotiation is not so much whether or not Greenland has the right to declare independence, but rather if it should take this step.